Concurrent alteration in inflammatory biomarker gene expression and oxidative stress: how aerobic training and vitamin D improve T2DM - Rastegar Hoseini; Hiwa Ahmed Rahim; Jalal Khdhr Ahmed (BMC, 2022)
Abstract Background Vitamin D (Vit D) supplementation and Aerobic Training (AT) exert several beneficial effects such as antioxidant and anti-inflammatory actions. The literature on the effects of AT and Vit D supplementation on the oxidative stress biomarkers and gene expression of inflammatory cytokines in patients with Type 2 Diabetes Mellitus (T2DM) is limited. The present study aimed to examine the effects of AT and Vit D supplementation on inflammation and oxidative stress signaling pathways in T2DM patients. Materials and methods In this single-blinded, randomized, placebo-controlled trial, 48 men with T2DM (aged 35-50 years with Body Mass Index (BMI) of 25-30 kg/m2) were randomly allocated into four groups: AT+Vit D (n = 10); AT + placebo (AT; n = 10); Vit D (n = 10), and Control + placebo (C; n = 10). The eight-week AT program was executed for 20-40 min/day, at 60-75% of heart rate maximum (HRmax), for 3 days/wks. The Vit D group received 50,000 IU of Vit D supplement capsules per week for 8 weeks. The serum levels of oxidative stress biomarkers and gene expression of inflammatory cytokines in the Peripheral Blood Mononuclear Cells (PBMCs) were evaluated using the RT-PCR method. To analyze the data, paired t-tests and one-way analysis of variance and Tukey's post hoc test were used at the significance level of P < 0.05. Results The result shows that serum 25-OH-Vit D, total nitrite, Total Glutathione (GSH), Total Antioxidant Capacity (TAC), Superoxide Dismutase (SOD), Catalase (CAT), and Glutathione Peroxidase (GPX) increased; and insulin, Fasting Blood Glucose (FBG), Homeostasis Model Assessment of Insulin Resistance (HOMA-IR), High Sensitivity C-Reactive Protein (hs-CRP), Malondialdehyde (MDA), glycated albumin, and Urinary 8-hydroxydeoxyguanine (8-OHdG) decreased significantly in all groups after 8 weeks, except for C. In addition, results of RT-PCR showed that AT+Vit D, Vit D, and AT significantly downregulated the gene expression of Tumor Necrosis Factor-Alpha (TNF-α), Interleukin-1 Beta (IL-1β), Mitogen-Activated Protein Kinases 1 (MAPK1), Nuclear Factor Kappa B (NF-κB) 1 (p50). It also upregulated Interleukin-4 (IL-4) gene expression, Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ) in T2DM patients compared to the C. Conclusion Additionally, the AT+Vit D group showed significantly lower insulin, FBG, HOMA-IR, hs-CRP, MDA, glycated albumin, urinary 8-OHdG, IL-1β, TNF-α, MAPK1, and NF-κB1 (p50) levels and significantly higher serum 25-OH-Vit D, total nitrite, GSH, TAC, CAT, SOD, GPX, IL-4, and PPAR-γ levels compared to the AT and Vit D groups. In T2DM patients, 8 weeks of AT+Vit D had a more significant impact on certain gene expressions related to inflammation and oxidative stress than Vit D or AT alone.